STEM Education for Young Women via Heroic Narratives: Evaluating the Heroine’s Learning Journey - Costa, Luis Felipe; Barbosa, Carlos Eduardo; Lima, Yuri; Nascimento, Luciana; Galeno, Larissa; Santos, Ana Moura; Xexéo, Geraldo; Souza, Jano Moreira de (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2024: Anais do IV Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2024.237408, 2024)
The Fostering Women to STEM MOOCs (FOSTWOM) project aims to increase the number of women in STEM careers through the participation of young women through free-access Massive Open Online Courses (MOOCs). One of its actions was the conception of the Heroine's Learning Journey (HLJ), a framework, separated into 12 stages, which employs a heroic narrative to inspire and empower young women, between ages 15 to 21, to persist in their pursuit of STEM studies. This framework is strategically tailored for online learning environments, specifically MOOCs. This study assesses the effectiveness of the HLJ through a survey involving 12 educational specialists affiliated with the FOSTWOM project. Results reveal that in terms of motivation capacity, all HLJ stages received a minimum of 60% positive ratings, and it was pointed out the need for improvement of two stages. Educators can harness the HLJ model to develop MOOCs that cater to gender equality needs within STEM fields.